A multi-state interferometer on an atom chip - J Petrovic; I Herrera; P Lombardi; F Schäfer; F S Cataliotti (New Journal of Physics, 2013)
Matter–wave interferometry is a powerful tool for high-precision measurements of the quantum properties of atoms, many-body phenomena and gravity. The most precise matter–wave interferometers exploit the excellent localization in momentum space and coherence of the degenerate gases. Further enhancement of the sensitivity and reduction of complexity are crucial conditions for the success and widening of their applications. Here we introduce a multi-state interferometric scheme that offers advances in both these aspects. The coherent coupling between Bose–Einstein condensates in different Zeeman states is used to generate high-harmonic output signals with an enhanced resolution and the maximum possible interferometric visibility. We demonstrate the realization of such an interferometer as a compact, easy to use, atom-chip device. This provides an alternative method for the measurement of the light–atom and surface–atom interactions and enables the application of multi-parameter sensing schemes in cold-atom interferometry.